2020
DOI: 10.1186/s41927-020-00126-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-world questions and concerns about disease-modifying antirheumatic drugs (DMARDs): a retrospective analysis of questions to a medicine call center

Abstract: Background: Disease-modifying antirheumatic drugs (DMARDs) have transformed the treatment of numerous autoimmune and inflammatory diseases but their perceived risk of harm may be a barrier to use. Methods: In a retrospective mixed-methods study, we analysed conventional (c) and biologic (b) DMARDs-related calls and compared them with rest of calls (ROC) from consumers to an Australian national medicine call center operated by clinical pharmacists from September 2002 to June 2010. This includes the period where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Over 20 years, the recorded number of ADRs related to DMARDs indicates a generally well-tolerated and manageable toxicity profile, although evidence of under-reporting [ 17 ]. In Australia, a retrospective analysis examined 1547 calls with an Australian medical call center involving both conventional and biologic DMARDs from September 2002 to June 2010 [ 18 ]. The study revealed that most patients' enquiries and concerns regarding DMARDs focused on their effectiveness and appropriate dosage rather than safety considerations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 20 years, the recorded number of ADRs related to DMARDs indicates a generally well-tolerated and manageable toxicity profile, although evidence of under-reporting [ 17 ]. In Australia, a retrospective analysis examined 1547 calls with an Australian medical call center involving both conventional and biologic DMARDs from September 2002 to June 2010 [ 18 ]. The study revealed that most patients' enquiries and concerns regarding DMARDs focused on their effectiveness and appropriate dosage rather than safety considerations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, a retrospective analysis examined 1547 calls with an Australian medical call center involving both conventional and biologic DMARDs from September 2002 to June 2010 [ 18 ]. The study revealed that most patients' enquiries and concerns regarding DMARDs focused on their effectiveness and appropriate dosage rather than safety considerations [ 18 ]. Some studies suggest that DMARDs rarely cause ADRs [ 11 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may overemphasize risk and overestimate the severity of potential side effects. 111 For example, patients with multiple myeloma who had previously experienced severe or life-threatening side effects put more importance on low toxicity than on progression-free survival. 107 …”
Section: Discussionmentioning
confidence: 99%
“…They may overemphasize risk and overestimate the severity of potential side effects. 111 For example, patients with multiple myeloma who had previously experienced severe or life-threatening side effects put more importance on low toxicity than on progression-free survival. 107 Another salient result is the increased acceptance of injectable treatments, notably self-administration, among patients who had already used this mode of administration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is growing evidence that the trade-offs between benefits and risks made by patients differ significantly from clinical experts [ 5 ]. Furthermore, patients with chronic conditions cautiously and deliberately reassess the benefits and risks of their treatments at multiple milestones in their disease journey and may overemphasize the potential risks of their current medicines or overestimate the benefits of new treatments [ 6 ]. The concept of a patient-based BRA of medicines has recently emerged and is attracting the attention of regulatory authorities who acknowledge the importance of incorporating patients' perspectives into their decision-making processes [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%